2021
DOI: 10.1111/1467-8268.12608
|View full text |Cite
|
Sign up to set email alerts
|

What drive gender gap in financial inclusion? Evidence from Cameroon

Abstract: This article analyses the drivers of the gender gap in financial inclusion in Cameroon, using Finscope 2017 data and Fairlie's decomposition method. We analyse six distinct financial inclusion variables captured by access to and use of financial inclusion products and services. The results of the decomposition show that there is a gap in all indicators of access to and use of financial products and services in favour of men. The results also show that the largest contributor to the gender gap in access to fina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 28 publications
(30 reference statements)
1
12
0
1
Order By: Relevance
“…They are therefore inclined to own a mobile account, which is much more accessible. These findings are supported by Ghosh and Vinod (2017) and Kumar et al (2019) in India, Mndolwa and Alhassan (2020) in Tanzania, and Ndoya and Tsala (2021) in Cameroon, who highlighted that the women are excluded from formal account through wage discrimination and lack of education. Although in urban areas, women have more access owing to there being less discrimination, they prefer informal services.…”
Section: Empirical Results and Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…They are therefore inclined to own a mobile account, which is much more accessible. These findings are supported by Ghosh and Vinod (2017) and Kumar et al (2019) in India, Mndolwa and Alhassan (2020) in Tanzania, and Ndoya and Tsala (2021) in Cameroon, who highlighted that the women are excluded from formal account through wage discrimination and lack of education. Although in urban areas, women have more access owing to there being less discrimination, they prefer informal services.…”
Section: Empirical Results and Discussionmentioning
confidence: 73%
“…Using the FinScope survey in Tanzania and Cameroon, Mndolwa and Alhassan (2020) and Ndoya and Tsala (2021) revealed that gender disparities in financial inclusion are higher in mobile money accounts, formal accounts and formal savings. While the over‐dependence of women on men and income deepen the gender gap in access to financial services, education expands the gender gap in the use of financial services.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The impact of an individual’s gender on financial access also varies with indicators defining financial inclusion. For instance, Ndoya and Tsala (2021) reported gender gap in all six financial inclusion indicators related to access and usage taken in their study when examined for Cameroon while the study in Tanzania (Mndolwa & Alhassan, 2020) found gender dummy to be negative and significant for determining formal savings, positive and significant for formal credit while insignificant for account ownership and mobile money accounts. Another study examining mobile money as a financial inclusion instrument in the context of Ghana found that males are less inclined to use mobile money when compared to females.…”
Section: Resultsmentioning
confidence: 98%
“…Au regard de l'importance des associations dans notre société, il ressort que 62,68% des enquêtés sont membres d'une association. L'on déplore la faiblesse d'accessibilité aux services bancaires (13,29%) et aux services de la microfinance (11,36%) laissant plus de place au développement des activités du mobile money, avec un accès favorable aux hommes (Ndoya & Tsala, 2021; Mndolwa & Alhassan, 2020), dans notre environnement. D'où la nécessité d'évaluer l'effet de cette innovation sur la capacité des ménages à faire face aux différents chocs économiques et sociaux affectant leur vie au quotidien.…”
Section: Methodologie Et Donneesunclassified